From lockdown to recovery: changing patterns of viral infection severity in a pediatric cohort with asthma - Jones, Cassidy; Laws, Matthew; Yousuf, Shahwar; Delo, Andrew; Hartzell, Susanna; Kinder, Emma; Ingold, Ashton; Boyanton, Bobby L.; Frederick, Dana; Frenner, Rachel A.; Hathorn, Erin; Mourani, Peter M.; et al. (Frontiers in Allergy, 2025)
BackgroundRespiratory viruses such as rhinovirus and respiratory syncytial virus (RSV) are common triggers of asthma exacerbations in children. The COVID-19 pandemic introduced non-pharmaceutical interventions (NPIs) that altered viral circulation; however, their long-term effects on pediatric asthma outcomes remain unclear.ObjectiveTo evaluate how the epidemiology and severity of respiratory viral infections in children with asthma changed before, during, and after COVID-19-related NPIs.MethodsWe conducted a cross-sectional analysis of pediatric asthma patients (ages 4–18) with laboratory-confirmed respiratory viral infections from 2018 to 2024 at Arkansas Children's (AC) and AC Northwest (ACNW). Viral detection was performed using the BioFire® Respiratory Panel. Clinical severity was evaluated using a modified World Health Organization Ordinal Scale for Clinical Improvement (mWHO OSI). Patients were categorized by period (pre-NPI, NPI, post-NPI), viral type, rurality, and Childhood Opportunity Index (COI).ResultsThis study included 9,391 pediatric asthma patients with laboratory-confirmed viral infections. RV/EV was the most common virus during all periods. Viral incidence decreased during NPIs but rebounded post-NPI with unusual seasonality. mWHO OSI scores declined over time (pre-NPI: 2.98; NPI: 2.49; post-NPI: 2.28), with significant reductions in hospitalizations, PICU admissions, and oxygen use (p < 0.0001). Severe disease (mWHO OSI 6–8) was infrequent. Rural and low-COI patients exhibited higher severity, although disparities narrowed post-NPI.ConclusionsNPIs were associated with sustained reductions in asthma-related illness severity, even with increased viral detection post-pandemic. These findings highlight the long-term impact of public health measures on pediatric asthma outcomes and emphasize the need for ongoing surveillance of respiratory viruses and health disparities.